Lynch syndrome caused by a pathogenic SINE-VNTR-Alu (SVA) insertion in MSH2 gene identified by long-read DNA sequencing - Jihoon E. Joo; Khalid Mahmood; Mark Clendenning; Peter Georgeson; Romy Walker; Julia Como; Fiona Phillips; Bernard J. Pope; Steven Batinovic; Natalie Diepenhorst; Julie McDonald; Toni Rice; et al. (Familial Cancer, 2026)
Lynch syndrome, the most common hereditary cancer syndrome, is caused by germline pathogenic variants in DNA mismatch repair (MMR) genes. Identifying complex or structural MMR gene pathogenic variants can be challenging with short-read sequencing resulting in patients with unexplained MMR-deficient tumours. In this study, we report multiple members of a family who developed MSH2-deficient tumours where clinical multi-gene panel testing of the DNA MMR genes using short-read sequencing did not find a germline pathogenic variant. Oxford Nanopore Technologies adaptive sampling (ONT-AS) long-read sequencing, targeting 104 hereditary cancer genes, identified a shared ~ 3.2 kb SINE-VNTR-Alu (SVA) family F retrotransposon insertion within exon 12 of MSH2 in both the proband and her father. Segregation of this MSH2 SVA insertion by targeted PCR confirmed three additional family members as carriers, including a paternal uncle with three colorectal cancers and an MSH2-deficient sebaceous adenoma. Three of the five heterozygous carriers were cancer affected with at least one MSH2-deficient tumour each. This study demonstrates that long-read sequencing can identify structural variants that are missed by current short-read sequencing multi-gene panel testing, improving the diagnosis of Lynch syndrome. These findings support incorporating long-read sequencing into routine diagnostic workflows for patients with suspected Lynch syndrome following a negative germline test.